Student’s Preferences Towards Parent’s Decisions in Family Business Management and its Impact on Learning Motivation - Elisabeth Marlina Sari Lintong (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the preferences of Management Study Program students at Universitas Pelita Harapan (UPH) Medan Campus regarding how their parents manage the family business and how these preferences influence students’ academic learning motivation. Data were collected from one hundred respondents representing the student population using a quantitative approach. The results of the analysis indicate that students’ preferences toward their parents’ decision-making in the family business have a significant effect on their motivation to learn; students who show stronger preferences for involvement in the family business tend to exhibit higher academic learning motivation. These results give parents and teachers fresh perspectives on how family business choices influence students' learning settings. Additionally, this study highlights the significance of creating holistic and integrative teaching methods, especially in situations when family financial decisions affect students' academic and professional growth. The results could be used as a basis for developing more flexible teaching methods in both formal education and family business management situations.